Outcomes of Minimally Invasive Colectomy for Perforated Diverticulitis. Issue 4 (April 2021) - Moghadamyeghaneh, Zhobin; Talus, Henry; Fitzgerald, Simon; Muthusamy, Muthukumar; Stamos, Michael J.; Roudnitsky, Valery
Background: We hypothesized that a laparoscopic approach to sigmoidectomy for perforated diverticulitis is associated with less morbidity and mortality. Methods: The NSQIP database was used to investigate adult patients who underwent emergent colectomy with end colostomy for perforated diverticulitis. A multivariate analysis using logistic regression was used to compare outcomes of patients by surgical approach. Results: We found a total of 2937 adult patients who underwent emergent colectomy for perforated diverticulitis during 2012-2017. The rate of minimally invasive surgery (MIS) was 11.4% with 38.6% conversion rate to open. The 30-day mortality and morbidity rates were 8.8% and 65.8%, respectively. Following adjustment using a multivariate analysis, the open approach was associated with higher morbidity (67.2% vs 56.8%, AOR: 1.70, P < .01) and mean hospitalization length of patients (13 days vs 10 days, P < .01) compared to the MIS approach. Respiratory complications of ventilator dependency (14.3% vs 6%, AOR: 2.95, P < .01) and unplanned intubation (7.4% vs 2.4%, AOR: 2.14, P = .03) were significantly higher in the open approach. However, patients who underwent the open approach were older (age >70; 33.5% vs 24%, P < .01) with more comorbid conditions such as COPD (10.8% vs 7.2%, P = .04) and CHF (9% vs 3.1%, P < .0). Conclusion: The MIS approach to emergent partial colectomy for perforated diverticulitis is associated with decreased morbidity and hospitalization length of patients. Utilization of the MIS approach for partial colectomy for perforated diverticulitis is 11.4% with a conversion rate of 38.6%. Efforts should be directed toward increasing the utilization of laparoscopic approaches for the surgical treatment of perforated diverticulitis.